Vocabulary Learning Strategies Among Malaysian Arabic Foreign Language Learners With Different Gender - Pisal, Nadhilah Abdul; Chulan, Majdah; Ismail, Ummi Syarah; Ismail, Noraini; Abdull Rahman, Nurul Labanihuda (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Having problems expanding vocabulary in a foreign language is one of the most common worries among students. Teaching students the right approach to learning is one way to assist them in overcoming this issue. Nevertheless, teachers must first be aware of the diverse vocabulary learning strategies used by students with varied preferences before disclosing the specific strategies to them. Therefore, this study was conducted to determine the types and levels of vocabulary learning strategies employed by students of different genders. Furthermore, it investigates whether there were significant differences in the use of strategies based on gender. The data was gathered using a vocabulary learning strategies questionnaire from 220 Arabic foreign language learners at Universiti Teknologi MARA (UiTM) Perlis Branch, Malaysia. The findings showed that male and female students used strategies at a moderate level. The dictionary strategy was the most frequently used among male and female students. However, these two groups of students utilized different least used strategies: metacognitive strategies for male students and practice strategies for female students. The findings also revealed no significant difference in the overall use of vocabulary learning strategies based on gender. This shows that the pattern of strategies used by male and female students was almost the same. Thus, educators can expose students to a variety of vocabulary learning strategies that serve as reinforcement from the beginning to help students' memory (memory strategies), improve their language skills (practice strategies), and manage their progression in vocabulary learning (metacognitive strategies).